Resin composition, and molded article and multilayer structure containing the same
By adding divalent metal hydroxide, monovalent metal compound and polyamide resin to the EVOH resin, the problems of long-term operationality and hue excellentness of the EVOH resin during the melt forming process are solved, and the stability and high-quality appearance of the molded product are achieved.
Patent Information
- Application Number
- CN202080090506.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-12-25
AI Technical Summary
The prior art is difficult to ensure the long-term operationality and hue excellence of ethylene-vinyl alcohol copolymer (EVOH) resins during the melt forming process, especially after repeated reuse.
By providing a resin composition, the composition comprises EVOH (A), a divalent metal hydroxide (B) and a monovalent metal compound (C) having an ethylene unit content of 20 mol % or more and 60 mol % or less, and a monovalent metal compound (C), and a polyamide resin (D) is added therein to improve the performance of the molded product.
The long-term operation and color performance of the EVOH resin during the melt forming process are achieved, ensuring the stability and appearance quality of the molded product during long-term use.
Smart Images

Figure DEST_PATH_IMAGE002 
Figure DEST_PATH_IMAGE004
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition containing an ethylene-vinyl alcohol copolymer, and a molded article and a multilayer structure containing the same. Background Art
[0002] Ethylene-vinyl alcohol copolymer (hereinafter sometimes abbreviated as EVOH) is widely used as various packaging materials such as films, sheets, and containers due to its excellent oxygen barrier properties. These packaging materials are generally formed by melt molding, and EVOH is required to have excellent appearance characteristics (less yellowing and other coloring) and excellent long-term running properties during melt molding.
[0003] In addition, EVOH has a plurality of highly reactive hydroxyl groups in its molecular structure. Therefore, when EVOH is continuously melt-molded for a long time, there are the following issues related to long-term operability: defects such as gel and particulate matter will increase over time, or streaky appearance defects will increase over time, and the commercial value of the molded product will decrease. It should be noted that regarding the long-term operability problems such as the increase of gel and particulate matter, the generation of streaky appearance defects, the type of problem that will occur will be different due to the differences in the equipment and operating conditions used in the molding process, and sometimes both problems will occur. In any case, it is desired to have an EVOH resin composition with excellent long-term operability with little change over time during long-term continuous operation.
[0004] Patent Document 1 discloses a resin composition, characterized in that it is a resin composition with EVOH as a main component, contains a phosphorus compound and a metal salt, the phosphorus compound is a condensed phosphoric acid, a compound having two or more phosphonic acid groups, or a combination thereof, the content of the phosphorus compound is 0.1 ppm or more and less than 50 ppm, and the content of the metal salt is 5 ppm or more and 500 ppm or less in terms of metal element conversion. According to this, a resin composition having excellent appearance characteristics in melt molding, long-term operation performance, and yellowing suppression even after repeated reuse, and a molded product obtained using the composition can be provided.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent document 1: WO2017 / 110568. Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, in recent years, the requirements for molded products in terms of color and appearance characteristics (gel, particles, stripes, etc.) have been increasing. In the resin composition containing a phosphorus compound and a metal salt described in Patent Document 1, although the long-term runnability is improved, the color and gas barrier properties during long-term melt molding are not necessarily sufficient. It is sought to provide a resin composition that can achieve both long-term runnability during melt molding and color during long-term melt molding.
[0010] The present invention is carried out in order to solve the above-mentioned problems, and its object is to provide a resin composition comprising EVOH having excellent long-term operation performance during melt forming and excellent hue in long-time melt forming. In addition, its object is to provide a molded product and a multilayer structure comprising the resin composition.
[0011] Means used to solve problems
[0012] In order to solve the above-mentioned problems, the present invention provides the following resin composition, and a molded article and a multilayer structure comprising the same.
[0013] That is, the present invention is achieved by providing the following technical solutions.
[0014] [1] a resin composition comprising an ethylene-vinyl alcohol copolymer (A) having an ethylene unit content of 20 mol% to 60 mol% (hereinafter sometimes abbreviated as "EVOH (A)"), a divalent metal hydroxide (B) and a monovalent metal compound (C), wherein the content of the divalent metal hydroxide (B) is 5 ppm to 5000 ppm, and the mass ratio C / B of the amount of the monovalent metal atom equivalent of the monovalent metal compound (C) to the amount of the divalent metal atom equivalent of the divalent metal hydroxide (B) is 0.025 to 100;
[0015] [2] The resin composition according to [1], comprising a polyamide resin (D) (hereinafter sometimes abbreviated as “PA(D)”);
[0016] [3] The resin composition according to [2], wherein the mass ratio (A / D) of EVOH (A) to PA (D) is 55 / 45 to 99 / 1;
[0017] [4] The resin composition according to [2] or [3], comprising a matrix phase comprising EVOH (A) and a dispersed phase comprising PA (D), wherein the dispersed phase comprising PA (D) has an average dispersed particle size of 2 μm or less;
[0018] [5] The resin composition according to [1] to [4], wherein 95% by mass or more of the thermoplastic resin constituting the resin composition is an ethylene-vinyl alcohol copolymer (A), or 95% by mass or more of the thermoplastic resin constituting the resin composition is an ethylene-vinyl alcohol copolymer (A) and a polyamide resin (D);
[0019] [6] The resin composition according to [1] to [5], wherein the content of the monovalent metal compound (C) in terms of monovalent metal atoms is 5 ppm or more and 1000 ppm or less;
[0020] [7] The resin composition according to [1] to [6], wherein the divalent metal atom constituting the divalent metal hydroxide (B) comprises at least one selected from the group consisting of magnesium, calcium, iron and zinc;
[0021] [8] The resin composition according to [1] to [7], wherein the ratio of magnesium atoms in all metal atoms constituting the divalent metal hydroxide (B) is 80 mol% or more;
[0022] [9] The resin composition according to [1] to [8], wherein the monovalent metal atom constituting the monovalent metal compound (C) comprises at least one selected from the group consisting of sodium, potassium, lithium, rubidium and cesium;
[0023]
[10] The resin composition according to [1] to [9], comprising a carboxylic acid;
[0024]
[11] The resin composition according to
[10] , comprising a higher fatty acid as the carboxylic acid, wherein the content of the higher fatty acid is 0.1 ppm to 250 ppm;
[0025]
[12] The resin composition according to [1] to
[11] , comprising a phosphoric acid compound;
[0026]
[13] The resin composition according to [1] to
[12] , wherein the aspect ratio of the divalent metal hydroxide (B) is 3 or more and 500 or less;
[0027]
[14] A molded article comprising the resin composition of [1] to
[13] ;
[0028]
[15] A multilayer structure comprising a layer made of the resin composition of [1] to
[13] .
[0029] Effects of the Invention
[0030] Effects of the Invention According to the present invention, there can be provided a resin composition comprising EVOH which is excellent in long-term runnability during melt molding and has excellent hue even during long-term melt molding. DETAILED DESCRIPTION
[0031] The resin composition of the present invention comprises EVOH (A) having an ethylene unit content of 20 mol% or more and 60 mol% or less, a divalent metal hydroxide (B) and a monovalent metal compound (C), wherein the content of the divalent metal hydroxide (B) is 5 ppm or more and 5000 ppm or less, and the mass ratio C / B of the monovalent metal atom conversion amount of the monovalent metal compound (C) to the divalent metal atom conversion amount of the divalent metal hydroxide (B) is 0.025 to 100. By satisfying this constitution, a resin composition having excellent long-term runnability during melt molding and excellent hue during long-term melt molding can be provided.
[0032] [EVOH(A)]
[0033] The resin composition of the present invention tends to exhibit excellent gas barrier properties by including EVOH (A). The EVOH (A) included in the resin composition of the present invention is a copolymer mainly composed of ethylene units and vinyl alcohol units, and is obtained by saponifying the vinyl ester units in an ethylene-vinyl ester copolymer. The EVOH (A) used in the present invention is not particularly limited, and a known substance used for melt molding purposes can be used. EVOH (A) can be used alone or in combination of two or more.
[0034] The ethylene unit content of EVOH (A) is 20 mol% or more and 60 mol% or less. When the ethylene unit content is less than 20 mol%, the melt moldability of the resin composition is likely to be reduced, preferably 24 mol% or more, more preferably 26 mol% or more. On the other hand, when the ethylene unit content exceeds 60 mol%, the gas barrier properties are likely to be reduced, preferably 48 mol% or less, more preferably 46 mol% or less.
[0035] The saponification degree of EVOH (A) is not particularly limited, but is preferably 95 mol% or more, more preferably 98 mol% or more, and further preferably 99 mol% or more from the viewpoint of maintaining gas barrier properties and exhibiting long-term operability. On the other hand, the upper limit of the saponification degree of EVOH (A) is preferably 100 mol%, more preferably 99.99 mol%. The saponification degree is a value measured in accordance with JIS K6726.
[0036] The lower limit of the melt flow rate of EVOH (A) (measured by the method described in ASTM D1238 under the conditions of a temperature of 210° C. and a load of 2160 g, hereinafter sometimes referred to as “melt flow rate”) is preferably 0.5 g / 10 min, more preferably 1.0 g / 10 min, and further preferably 2.0 g / 10 min. On the other hand, the upper limit of MFR is preferably 100 g / 10 min, more preferably 50 g / 10 min, and further preferably 25 g / 10 min. When MFR is within the above range, the moldability and processability of the resin composition are improved.
[0037] EVOH (A) may have units derived from other monomers other than ethylene and vinyl esters and saponified products thereof. When EVOH (A) has the aforementioned other monomer units, the content of the aforementioned other monomer units of EVOH (A) relative to all structural units is preferably 30 mol % or less, more preferably 20 mol % or less, further preferably 10 mol % or less, and particularly preferably 5 mol % or less. In addition, when EVOH (A) has units derived from the aforementioned other monomers, the lower limit may be 0.05 mol % or 0.10 mol %. Examples of the other monomers include olefins such as propylene, butene, pentene, and hexene; 3-acyloxy-1-propylene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-hexene, 5,6-diacyloxy-1-hexene; , 1,3-diacetoxy-2-methylenepropane and other olefins having ester groups or saponification products thereof; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid or their anhydrides, salts, or monoalkyl esters or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids such as vinyl sulfonic acid, allyl sulfonic acid, and methyl allyl sulfonic acid or their salts; vinyl silane compounds such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxy-ethoxy) silane, and γ-methacryloxypropyl methoxysilane; alkyl vinyl ethers, vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, vinylidene chloride, etc. EVOH (A) can be post-modified by methods such as carbamateization, acetalization, cyanoethylation, and oxyalkyleneation.
[0038] As a method for producing EVOH (A), for example, ethylene-vinyl ester copolymers can be produced according to a known method, and then EVOH (A) can be produced by saponifying them. Ethylene-vinyl ester copolymers are obtained by, for example, polymerizing ethylene and vinyl ester in an organic solvent such as methanol, tert-butyl alcohol, dimethyl sulfoxide, etc. under pressure using a free radical polymerization initiator such as benzoyl peroxide, azobisisobutyronitrile, etc. As raw material vinyl esters, vinyl acetate, vinyl propionate, vinyl pivalate, etc. can be used, and among these, vinyl acetate is preferred. The saponification of ethylene-vinyl ester copolymers can use an acid catalyst or a base catalyst. Regarding the saponification method, both continuous and intermittent methods are possible. As base catalysts, sodium hydroxide, potassium hydroxide, alkali metal alkoxides, etc. can be used.
[0039] In this way, a solution containing EVOH (A) is obtained, and then the solvent is removed. The method for removing the solvent is not particularly limited as long as it is a method that can reduce the solvent content. The EVOH solution is solidified by extruding it into a poor solvent such as water, thereby reducing the solvent content. In addition, the water can be mechanically squeezed out in an extruder or kneader, or the water vapor can be evaporated from the vents. After the solvent is removed in this way, EVOH (A) pellets are obtained by cutting. The method for obtaining EVOH (A) pellets by cutting is not particularly limited. The solidified water-containing strands can be cut by a cutter. For the material after the water content is reduced in the extruder or kneader, it can also be cut directly with a heating cutter or an underwater cutter in a flowing state.
[0040] [Divalent metal hydroxide (B)]
[0041] The resin composition of the present invention comprises a divalent metal hydroxide (B) of more than 5ppm and less than 5000ppm. The content of the divalent metal hydroxide (B) is preferably more than 10ppm, more preferably more than 15ppm, and further preferably more than 20ppm. If the content of the divalent metal hydroxide (B) is less than 5ppm, the tendency of long-term operation deterioration during melt forming is presented. In addition, the content of the divalent metal hydroxide (B) is preferably less than 3000ppm, more preferably less than 2500ppm, further preferably less than 1500ppm, and particularly preferably less than 400ppm. If the content of the divalent metal hydroxide (B) exceeds 5000ppm, the tendency of hue deterioration during long-term melt forming is presented.
[0042] When the resin composition of the present invention does not contain PA (D) described later, from the viewpoint of long-term operability during melt molding, the content of divalent metal hydroxide (B) in the resin composition of the present invention is preferably 10 ppm or more, more preferably 15 ppm or more, and further preferably 20 ppm or more. In addition, when PA (D) described later is not contained, from the viewpoint of hue during long-term melt molding, the content of divalent metal hydroxide (B) is preferably 1500 ppm or less, more preferably 1100 ppm or less, and further preferably 400 ppm or less. It should be noted that when the resin composition of the present invention does not contain PA (D) described later, if a fatty acid divalent metal salt such as a divalent metal acetate is used instead of the divalent metal hydroxide (B), the hue tends to deteriorate.
[0043] When the resin composition of the present invention includes PA (D) described later, from the viewpoint of long-term operability during melt molding, the content of the divalent metal hydroxide (B) is preferably 30 ppm or more, more preferably 50 ppm or more, and further preferably 70 ppm or more. In addition, from the viewpoint of hue during long-term melt molding, the content of the divalent metal hydroxide (B) is preferably 3500 ppm or less, more preferably 2800 ppm or less, further preferably 1100 ppm or less, and particularly preferably 500 ppm or less. It should be noted that when the resin composition of the present invention includes PA (D) described later, if a divalent metal carboxylate such as a divalent metal acetate is used instead of the divalent metal hydroxide (B), the appearance after the steaming treatment tends to deteriorate.
[0044] In the resin composition of the present invention, the content of the divalent metal atom conversion of the divalent metal hydroxide (B) is preferably 2 ppm or more and 3500 ppm or less. By making the content of the divalent metal atom conversion in the above range, the long-term operation performance during melt forming is excellent and the hue is also excellent in long-term melt forming. The content of the divalent metal atom conversion is preferably 4 ppm or more, more preferably 6 ppm or more, and more preferably 8 ppm or more. In addition, the content of the divalent metal atom conversion is preferably 1500 ppm or less, more preferably 1000 ppm or less, and more preferably 400 ppm or less.
[0045] In the resin composition of the present invention, when PA (D) described later is not contained, the content of the aforementioned divalent metal atoms is preferably 2 ppm or more and 2000 ppm or less. By making the content of the aforementioned divalent metal atoms in the above range, the long-term operation performance during melt forming is excellent, and the color is also excellent in the long-term melt forming. The content of the aforementioned divalent metal atoms is preferably 4 ppm or more, more preferably 6 ppm or more, and further preferably 8 ppm or more. On the other hand, the content of the aforementioned divalent metal atoms is preferably 1500 ppm or less, more preferably 600 ppm or less, and further preferably 100 ppm or less.
[0046] In addition, when the resin composition of the present invention contains PA (D) described later, the content of the aforementioned divalent metal atom conversion is preferably 12 ppm or more, more preferably 20 ppm or more, and further preferably 32 ppm or more. On the other hand, the content of the aforementioned divalent metal atom conversion is preferably 1400 ppm or less, more preferably 1100 ppm or less, further preferably 450 ppm or less, and particularly preferably 200 ppm or less.
[0047] The aspect ratio of the divalent metal hydroxide (B) is not particularly limited, and is preferably greater than 3 and less than 500. The aspect ratio of the divalent metal hydroxide (B) is more preferably greater than 8, further preferably greater than 12, and particularly preferably greater than 25. In addition, the aspect ratio of the divalent metal hydroxide (B) is more preferably less than 400, further preferably less than 300, and particularly preferably less than 100. If the aspect ratio of the divalent metal hydroxide (B) is within the above range, a good gas barrier property under high humidity is shown. The reason is still uncertain, but this tendency is a specific tendency that cannot be obtained in the evaluation of gas barrier properties under low humidity. It should be noted that the aspect ratio is a value obtained by the SEM method based on the arithmetic average of the measured values of the primary particle width (major diameter) and the primary particle thickness (minor diameter) of any 100 crystals in the SEM photograph.
[0048] The divalent metal atom constituting the divalent metal hydroxide (B) is not particularly limited, but preferably contains at least one selected from the group consisting of magnesium, calcium, iron and zinc. Among them, from the viewpoint of long-term operability in long-term melt molding, the divalent metal atom constituting the divalent metal hydroxide (B) is more preferably at least one selected from the group consisting of magnesium, calcium and zinc, further preferably at least one selected from the group consisting of magnesium and calcium, and particularly preferably magnesium.
[0049] As the divalent metal hydroxide (B), hydroxides containing the above-mentioned divalent metal atoms can be cited, preferably containing at least one selected from the group consisting of magnesium hydroxide, calcium hydroxide, iron hydroxide and zinc hydroxide. Among them, from the viewpoint of long-term operation in long-term melt molding, at least one selected from the group consisting of magnesium hydroxide, calcium hydroxide and zinc hydroxide is more preferred, at least one selected from the group consisting of magnesium hydroxide and calcium hydroxide is further preferred, and magnesium hydroxide is particularly preferred.
[0050] The ratio of one metal atom selected from the group consisting of magnesium, calcium and zinc in all the metal atoms constituting the divalent metal hydroxide (B) is preferably 80 mol% or more, more preferably 90% or more, further preferably 95% or more, and the metal atoms constituting the divalent metal hydroxide (B) are particularly preferably composed of only one metal atom selected from the group consisting of magnesium, calcium and zinc. Thus, there is an advantage of excellent long-term operation in long-term melt forming. Among them, the ratio of magnesium atoms in all the metal atoms constituting the divalent metal hydroxide (B) is preferably 80 mol% or more, more preferably 90% or more, further preferably 95% or more, and the metal atoms constituting the divalent metal hydroxide (B) are particularly preferably composed of only magnesium atoms. By making the ratio of magnesium atoms more than 80 mol%, a tendency of particularly excellent long-term operation in long-term melt forming is presented.
[0051] [Monovalent metal compound (C)]
[0052] The resin composition of the present invention comprises a monovalent metal compound (C), and the mass ratio C / B of the monovalent metal atom conversion amount of the monovalent metal compound (C) relative to the divalent metal atom conversion amount of the divalent metal hydroxide (B) is 0.025 to 100. The aforementioned mass ratio C / B is preferably 0.2 or more, more preferably 1.0 or more, further preferably 1.5 or more, and particularly preferably 2.0 or more. If the aforementioned mass ratio C / B is less than 0.025, there is a tendency for long-term operation performance to deteriorate during melt molding. In addition, the aforementioned mass ratio C / B is preferably 80 or less, more preferably 60 or less, further preferably 50 or less, and particularly preferably 30 or less. If the aforementioned mass ratio C / B exceeds 100, there is a tendency for the hue to deteriorate during long-term melt molding.
[0053] In addition, when the resin composition of the present invention does not contain PA (D) described later, the mass ratio C / B is preferably 0.05 or more, more preferably 0.2 or more, further preferably 0.3 or more, particularly preferably 1.2 or more, and most preferably 2.5 or more. In addition, the mass ratio C / B is preferably 80 or less, more preferably 60 or less, and further preferably 50 or less. If the mass ratio C / B exceeds 100, there is a tendency for the hue to deteriorate during long-term melt molding.
[0054] In addition, when the resin composition of the present invention contains PA (D) described later, the mass ratio C / B is preferably 0.05 or more, more preferably 0.2 or more, further preferably 0.3 or more, particularly preferably 1.2 or more, and most preferably 2.0 or more. In addition, the mass ratio C / B is preferably 80 or less, more preferably 60 or less, and further preferably 50 or less. If the mass ratio C / B exceeds 100, there is a tendency for the hue to deteriorate during long-term melt molding.
[0055] The content of the monovalent metal atom conversion of the monovalent metal compound (C) in the resin composition of the present invention is preferably 5ppm or more, more preferably 30ppm or more, further preferably 50ppm or more, and particularly preferably 80ppm or more. If the content of the monovalent metal atom conversion is 5ppm or more, there is a tendency for good long-term operation during melt forming. In addition, the content of the monovalent metal atom conversion is preferably 1000ppm or less, more preferably 750ppm or less, further preferably 500ppm or less, and particularly preferably 250ppm or less. If the content of the monovalent metal atom conversion is 1000ppm or less, there is a tendency to suppress the deterioration of the hue during long-term melt forming.
[0056] The monovalent metal atom constituting the monovalent metal compound (C) is not particularly limited, but preferably contains at least one selected from the group consisting of sodium, potassium, lithium, rubidium and cesium. Among them, from the viewpoint of long-term operability during melt molding, the monovalent metal atom constituting the monovalent metal compound (C) is more preferably at least one selected from the group consisting of sodium and potassium, and particularly preferably sodium.
[0057] Specific examples of the monovalent metal compound (C) include salts of organic acids such as aliphatic carboxylic acids, aromatic carboxylic acids, aliphatic dicarboxylic acids, aromatic dicarboxylic acids, tricarboxylic acids, tetracarboxylic acids, hydroxycarboxylic acids, ketodicarboxylic acids, and amino acids containing the above-mentioned monovalent metal atoms; salts of inorganic acids such as sulfuric acid, sulfurous acid, carbonic acid, and phosphoric acid; and metal complexes. Examples thereof include sodium acetate, potassium acetate, sodium phosphate, lithium phosphate, sodium stearate, potassium stearate, and sodium salt of ethylenediaminetetraacetic acid. Among them, at least one selected from the group consisting of sodium acetate, potassium acetate, and sodium phosphate is suitable.
[0058] [carboxylic acid]
[0059] The resin composition of the present invention preferably includes carboxylic acid. As carboxylic acid, it is suitable to adopt at least one selected from the group consisting of lower fatty acids of 1 to 7 carbon atoms and higher fatty acids of 8 to 30 carbon atoms, more preferably including both the aforementioned lower fatty acids and the aforementioned higher fatty acids. As lower fatty acids of 1 to 7 carbon atoms, oxalic acid, succinic acid, benzoic acid, citric acid, acetic acid, lactic acid, etc. can be exemplified. Among these, from the viewpoints of cost, ease of acquisition, etc., acetic acid is preferably used. In addition, as higher fatty acids of 8 to 30 carbon atoms, stearic acid, lauric acid, montanic acid, behenic acid, caprylic acid, sebacic acid, ricinoleic acid, myristic acid, palmitic acid, etc. can be exemplified. Among these, from the viewpoint of dispersibility, stearic acid is preferably used.
[0060] As the content of the carboxylic acid included in the resin combination of the present invention, it is not particularly limited, but is preferably more than 0.1ppm and less than 2000ppm. By making the content of the carboxylic acid be in the above-mentioned scope, there is the advantage of being able to suppress the deterioration of the hue and phase in the long-time melt forming. Especially, the content of the aforementioned lower fatty acid is more preferably more than 10ppm, further preferably more than 30ppm, particularly preferably more than 50ppm, and most preferably more than 80ppm. On the other hand, the content of the aforementioned lower fatty acid is more preferably less than 1500ppm, further preferably less than 1000ppm, and particularly preferably less than 500ppm.
[0061] The resin composition of the present invention preferably comprises a higher fatty acid as the aforementioned carboxylic acid, and the content of the aforementioned higher fatty acid is more than 0.1ppm and less than 250ppm. By making the content of the aforementioned higher fatty acid be in the above-mentioned range, there is the advantage of improving the dispersibility of the divalent metal hydroxide (B). The content of the aforementioned higher fatty acid is more preferably more than 0.2ppm, more preferably more than 0.5ppm, and particularly preferably more than 1ppm. On the other hand, the content of the aforementioned higher fatty acid is more preferably less than 200ppm, more preferably less than 100ppm, and particularly preferably less than 50ppm.
[0062] [Phosphoric acid compounds]
[0063] The resin composition of the present invention preferably contains a phosphoric acid compound. As the phosphoric acid compound, various acids such as phosphoric acid and phosphorous acid, and salts thereof, etc. can be exemplified. As the phosphate, it can be contained in any form of dihydrogen phosphate, dihydrogen phosphate, and phosphate, and its cation type is not particularly limited, preferably an alkali metal salt and an alkaline earth metal salt. Among them, it is preferred to add the phosphoric acid compound in the form of sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate.
[0064] The content of the phosphate compound included in the resin composition of the present invention is not particularly limited, and is preferably more than 1ppm and less than 1000ppm in terms of phosphate conversion. By making the content of the aforementioned phosphate compound in the above range, there is an advantage of being able to suppress the deterioration of the hue during long-term melt forming. The content of the aforementioned phosphate compound is more preferably more than 3ppm, more preferably more than 5ppm, and particularly preferably more than 10ppm. On the other hand, the content of the aforementioned phosphate compound is more preferably less than 800ppm, more preferably less than 500ppm, and particularly preferably less than 300ppm.
[0065] [PA(D)]
[0066] The resin composition of the present invention is also preferably a form containing PA (D). By containing PA (D), the following effects are exerted: excellent long-term runnability during melt molding, excellent color during long-term melt molding, and excellent appearance after hot water treatment such as retort treatment (retort resistance). Examples of PA (D) include polycaproamide (nylon 6), poly-ω-aminoheptanoic acid (nylon 7), poly-ω-aminononanoic acid (nylon 9), polyundecanamide (nylon 11), polylaurolactam (nylon 12), polyethylene adipamide (nylon 26), polybutylene adipamide (nylon 46), polyhexamethylene adipamide (nylon 66), polyhexamethylene sebacate (nylon 610), polyhexamethylene dodecanoic acid (nylon 612), polyoctyl adipamide (nylon 86), polydecane adipamide (nylon 106), caprolactam / laurolactam copolymer (nylon 6 / 12), caprolactam / ω-aminononanoic acid copolymer (nylon 6 / 9), caprolactam / hexamethylene diammonium adipate copolymer (nylon 6 / 66), laurolactam / hexamethylene diammonium adipate copolymer (nylon 12 / 66), ethylene diammonium adipate / hexamethylenediammonium adipate copolymer (nylon 26 / 66), caprolactam / hexamethylenediammonium adipate / hexamethylenediammonium sebacate copolymer (nylon 6 / 66 / 610), ethylenediammonium adipate / hexamethylenediammonium adipate / hexamethylenediammonium sebacate copolymer (nylon 26 / 66 / 610), polyhexamethyleneisophthalamide (nylon 6I), polyhexamethyleneterephthalamide (nylon 6T), hexamethyleneisophthalamide / hexamethyleneterephthalamide copolymer (nylon 6I / 6T), 11-aminoundecanoic acid / hexamethyleneterephthalamide copolymer, polynonaneterephthalamide (nylon 9T), polydecaneterephthalamide (nylon 10T), polyhexamethylenecyclohexylamide, polynonamethylenecyclohexylamide, or those obtained by modifying these polyamides with aromatic amines such as methylenebenzylamine and meta-xylylenediamine. In addition, meta-xylylenediammonium adipate and the like are also mentioned.
[0067] Among these, polyamide resins mainly composed of caproamide are preferred from the viewpoint of improving the appearance after hot water treatment such as retorting treatment. Specifically, it is preferred that 75 mol % or more of the structural units of PA (D) are caproamide units. Among them, PA (D) is preferably nylon 6 from the viewpoint of compatibility with EVOH (A).
[0068] The polymerization method of PA(D) is not particularly limited, and a known method such as melt polymerization, interfacial polymerization, solution polymerization, bulk polymerization, solid phase polymerization, or a combination thereof can be employed.
[0069] When the resin composition of the present invention contains PA (D), the mass ratio (A / D) of EVOH (A) to PA (D) is preferably 55 / 45 to 99 / 1. When the mass ratio (A / D) is less than 55 / 45, the color may deteriorate during long-term melt molding, and it is more preferably 60 / 40 or more, further preferably 70 / 30 or more, and particularly preferably 80 / 20 or more. On the other hand, when the mass ratio (A / D) exceeds 99 / 1, the appearance after hot water treatment such as retorting may become insufficient, and it is more preferably 95 / 5 or less.
[0070] When the resin composition of the present invention contains PA(D), it preferably has a matrix phase containing EVOH(A) and a dispersed phase containing PA(D), and the average dispersed particle size of the dispersed phase containing the aforementioned PA(D) is less than 2 μm. The average dispersed particle size of the dispersed phase containing PA(D) represents: the average dispersed particle size of the dispersed phase dispersed in EVOH(A) as the matrix phase. The dispersed phase is essentially made of PA(D) only, and may also contain resins other than PA(D) in the dispersed phase. The content of resins other than PA(D) contained in the dispersed phase is generally less than 50% by mass. Here, the average dispersed particle size is calculated as follows: the particle size of the dispersed phase containing 100 PA(D) particles falling within the field of view is observed using an electron microscope, and the average value thereof is calculated as the average dispersed particle size. When the particles are in a shape other than a circle, such as an ellipse, the value of the major diameter is used for calculation. If the average dispersed particle size of the dispersed phase containing PA (D) is 2 μm or less, the appearance after the steaming treatment tends to be excellent. The above average dispersed particle size is more preferably 1 μm or less, further preferably 0.5 μm or less, and particularly preferably 0.2 μm or less. The average dispersed particle size of the dispersed phase containing PA (D) can be 0.01 μm or more. The dispersed particle size of PA (D) can be adjusted to a suitable range by changing the addition method and addition order of EVOH (A), divalent metal hydroxide (B), monovalent metal compound (C), and PA (D), the resin temperature during kneading, the screw structure, the screw speed, the residence time, etc.
[0071] As a thermoplastic resin constituting the resin composition of the present invention, it is a suitable embodiment to include the above-mentioned PA (D) in addition to EVOH (A), but other thermoplastic resins other than EVOH (A) and PA (D) may be included within the range that does not impair the effect of the present invention. As the other thermoplastic resin, thermoplastic resins such as polyolefins, polyesters, polystyrenes, polyvinyl chlorides, acrylic resins, polyurethanes, polycarbonates, and polyvinyl acetates can be listed. The content of the other thermoplastic resin is usually less than 5% by mass. When the resin composition of the present invention does not contain PA (D), as a thermoplastic resin constituting the resin composition of the present invention, from the viewpoint of being able to further exert the gas barrier effect derived from EVOH (A), preferably 90% by mass or more is EVOH (A), more preferably 97% by mass or more is EVOH (A), further preferably 99% by mass or more is EVOH (A), and particularly preferably substantially only EVOH (A) is composed. When the resin composition of the present invention contains PA (D), from the viewpoint of further improving the appearance characteristics after retorting treatment, the thermoplastic resin constituting the resin composition of the present invention preferably comprises EVOH (A) and PA (D) in an amount of 95% by mass or more, more preferably EVOH (A) and PA (D) in an amount of 97% by mass or more, further preferably EVOH (A) and PA (D) in an amount of 99% by mass or more, and particularly preferably substantially consisting of only EVOH (A) and PA (D).
[0072] In the resin composition of the present invention, various additives other than the above can be mixed within the range that does not damage the effect of the present invention. Examples of such additives include antioxidants, plasticizers, heat stabilizers, ultraviolet absorbers, antistatic agents, lubricants, colorants, fillers, other resins, etc., and the following examples can be specifically listed. The content of the additive is usually 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less.
[0073] Antioxidants: 2,5-di-tert-butylhydroquinone, 2,6-di-tert-butyl-p-cresol, 4,4'-thiobis(6-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate, 4,4'-thiobis(6-tert-butylphenol), etc.
[0074] Plasticizers: diethyl phthalate, dibutyl phthalate, dioctyl phthalate, wax, liquid paraffin, phosphate ester, etc.;
[0075] Ultraviolet absorbers: ethylene-2-cyano-3,3'-diphenylacrylate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)5-chlorobenzotriazole, 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, etc.
[0076] Antistatic agent: pentaerythritol monostearate, sorbitan monopalmitate, sulfated polyolefins, polyethylene oxide, etc.
[0077] Lubricant: vinyl bis stearamide, butyl stearate, etc.
[0078] When the resin composition of the present invention does not contain PA (D), the proportion of EVOH (A), divalent metal hydroxide (B) and monovalent metal compound (C) in the resin composition of the present invention is preferably 95% by mass or more, more preferably 98% by mass or more, and further preferably 99% by mass or more. It is particularly preferred that the resin composition of the present invention consists essentially of only EVOH (A), divalent metal hydroxide (B) and monovalent metal compound (C). In addition, when the resin composition of the present invention contains PA (D), the proportion of EVOH (A), divalent metal hydroxide (B), monovalent metal compound (C) and PA (D) in the resin composition of the present invention is preferably 95% by mass or more, more preferably 98% by mass or more, and further preferably 99% by mass or more. It is particularly preferred that the resin composition of the present invention consists essentially of only EVOH (A), divalent metal hydroxide (B), monovalent metal compound (C) and PA (D).
[0079] The method for producing the resin composition of the present invention is not particularly limited, and it is preferably prepared by adding various additives such as divalent metal hydroxides (B), monovalent metal compounds (C) and carboxylic acids to EVOH (A), and melt-kneading. In the case of containing PA (D), it is preferably prepared by dry-mixing EVOH (A) and PA (D), and then melt-kneading. Specifically, a known mixing device or kneading device such as a mixer, an extruder, an open roll, a Banbury mixer, etc. can be used. The temperature during melt-kneading is generally 110 to 300°C. The divalent metal hydroxide (B), the monovalent metal compound (C) and various additives may be pre-contained in EVOH (A) or PA (D).
[0080] The resin composition of the present invention may be in any form such as pellets and powders, and is preferably a pellet from the viewpoint of being able to stably perform melt forming. When EVOH (A) is a pellet, the following method is suitable: the EVOH (A) pellets are impregnated with a solution containing various additives such as a monovalent metal compound (C) and a carboxylic acid, and dried, thereby obtaining dry EVOH (A) pellets, and then dry-mixed with a divalent metal hydroxide (B). As the moisture content of the dry EVOH (A) pellets, from the viewpoint of preventing adverse conditions during melt forming, it is preferably 1% by mass or less, and more preferably 0.5% by mass or less. As carboxylic acids, when using lower fatty acids with 1 to 7 carbon atoms and higher fatty acids with 8 to 30 carbon atoms, the lower fatty acids are preferably contained in the solution, and the higher fatty acids are preferably added when the dry EVOH (A) pellets are dry-mixed with the divalent metal hydroxide (B).
[0081] Examples of uses of the resin composition of the present invention include extrusion molded products, films or sheets (especially stretched films or heat shrinkable films), thermoformed products, wallpapers or decorative panels, pipes or hoses, irregularly shaped molded products, extrusion blow molded products, injection molded products, flexible packaging materials, containers (especially retort containers), etc. When the molded product is a multilayer structure, it is preferably a coextruded film or coextruded sheet, a heat shrinkable film, a container (especially a coextrusion blow molded container, a co-injection molded container, a retort container), a pipe (especially a fuel pipe or a warm water circulation pipe), a hose (especially a fuel hose), etc.
[0082] When the molded product of the present invention is a multilayer structure comprising a layer with a resin composition of the present invention, the multilayer structure is formed by stacking other layers different from the layer made by the resin composition of the present invention. As the layer composition of the multilayer structure of the present invention, if the layer made by the polymer except the resin composition of the present invention is recorded as the x layer, the layer made by the resin composition of the present invention is recorded as the y layer, and the adhesive polymer layer is recorded as the z layer, then x / y, x / y / x, x / z / y, x / z / y / z / x, x / y / x / y / x, x / z / y / z / x / z / y / z / x etc. can be illustrated. When multiple x layers are set, their kind can be the same or different. In addition, the layer obtained by using the recycled polymer composed of the waste materials such as the scraps produced when forming can be separately provided, and the recycled polymer can also be blended in the layer made by other polymers. The thickness of each layer of the multilayer structure is not particularly limited, and from the viewpoints such as formability and cost, the thickness ratio of the y layer relative to the thickness of all layers is preferably 2 ~ 20%.
[0083] The polymer used in the above-mentioned x-layer is preferably a thermoplastic polymer from the viewpoint of processability, etc. Examples of the thermoplastic polymer include the following polymers.
[0084] ・Polyethylene, polypropylene, ethylene-propylene copolymers, ethylene or propylene copolymers (copolymers of ethylene or propylene and at least one of the following monomers: α-olefins such as 1-butene, isobutylene, 4-methyl-1-pentene, 1-hexene, and 1-octene; unsaturated carboxylic acids such as itaconic acid, methacrylic acid, acrylic acid, and maleic anhydride, their salts, partial esters or full esters, nitriles, amides, and anhydrides; vinyl carboxylate vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl octanoate, vinyl dodecanoate, vinyl stearate, and vinyl arachidonic acid; vinyl silane compounds such as vinyl trimethoxysilane; unsaturated sulfonic acids or their salts; alkyl mercaptans; vinyl pyrrolidones, etc.);
[0085] ・Polyolefins such as poly-4-methyl-1-pentene and poly-1-butene;
[0086] ・Polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate;
[0087] ・Polyamides such as poly-ε-caprolactam, polyhexamethylene adipamide, and poly-m-xylylene adipamide;
[0088] ・Polyvinylidene chloride, polyvinyl chloride, polystyrene, polyacrylonitrile, polycarbonate, polyacrylate, etc.
[0089] The thermoplastic polymer layer may be unstretched, uniaxially or biaxially stretched or calendered.
[0090] Among these thermoplastic polymers, polyolefins are preferred from the viewpoints of moisture resistance, mechanical properties, economic efficiency, heat sealability, and the like, and polyamides and polyesters are preferred from the viewpoints of mechanical properties, heat resistance, and the like.
[0091] On the other hand, as the adhesive polymer used in the z layer, any one can be used as long as it can bond the layers together, and preferably a polyurethane or polyester-based one-component or two-component curable adhesive, a carboxylic acid-modified polyolefin polymer, etc. The carboxylic acid-modified polyolefin polymer is an olefin polymer or copolymer containing an unsaturated carboxylic acid or its anhydride (maleic anhydride, etc.) as a copolymer component; or a graft copolymer obtained by grafting an unsaturated carboxylic acid or its anhydride to an olefin polymer or copolymer.
[0092] When a multilayer structure is manufactured by co-injection molding, co-extrusion molding, etc., the adhesive polymer is more preferably a carboxylic acid-modified polyolefin polymer. In particular, when the x layer is a polyolefin polymer, the adhesion to the y layer becomes good. As the polyolefin polymer constituting the carboxylic acid-modified polyolefin polymer, polyethylene such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-low-density polyethylene (VLDPE) can be listed; polypropylene; copolymerized polypropylene; ethylene-vinyl acetate copolymer; ethylene-(methyl)acrylate (methyl or ethyl) copolymer, etc. On the other hand, when a multilayer structure is manufactured by dry lamination, a polyurethane-based two-component curable adhesive is more preferred. At this time, a variety of polymers can be used in the x layer, so the function of the multilayer structure can be further improved.
[0093] Examples of methods for obtaining the multilayer structure include extrusion lamination, dry lamination, co-injection molding, co-extrusion molding, etc. Examples of co-extrusion molding include co-extrusion lamination, co-extrusion sheet molding, co-extrusion pipe molding, co-extrusion tube molding, co-extrusion inflation molding, and co-extrusion blow molding.
[0094] The sheets, films, parisons, etc. of the aforementioned multilayer structure obtained in this way are reheated at a temperature below the melting point of the polymer contained therein, and uniaxially stretched or biaxially stretched by thermoforming methods such as deep drawing, roll stretching, pantograph stretching, inflation stretching, blow molding, etc., to obtain stretched molded products.
[0095] The molded article containing the resin composition of the present invention thus obtained exhibits the effects of excellent long-term running properties and excellent color tone, and particularly when PA(D) is contained, excellent appearance after hot water treatment such as retorting. Example
[0096] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. It should be noted that the measurement, calculation and evaluation methods were respectively in accordance with the following methods.
[0097] <Raw materials used>
[0098] [Divalent metal hydroxide (B)]
[0099] ・B-1: Magnesium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., aspect ratio: 10)
[0100] ・B-2: Magnesium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., aspect ratio: 23)
[0101] ・B-3: Magnesium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., powder)
[0102] ・B-4: KISUMA (registered trademark) 10A (manufactured by Kyowa Chemical Industry Co., Ltd., magnesium hydroxide, aspect ratio: 67)
[0103] ・B-5: KISUMA (registered trademark) 5A (manufactured by Kyowa Chemical Industry Co., Ltd., magnesium hydroxide, aspect ratio: 4)
[0104] ・B-6: Calcium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0105] ・B-7: Zinc hydroxide (manufactured by Junsei Chemical Co., Ltd.).
[0106] [Metal compound (B')]
[0107] ・B'-8: Aluminum hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0108] ・B'-9: Magnesium acetate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0109] ・B'-10: Magnesium stearate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0110] The aspect ratios described in the divalent metal hydroxide (B) and the metal compound (B′) are values obtained by SEM method and by arithmetic average of the primary particle widths (longer diameter) and primary particle thicknesses (shorter diameter) of any 100 crystals in the SEM photograph.
[0111] [Monovalent metal compound (C)]
[0112] ・C-1: Sodium acetate
[0113] ・C-2: Potassium acetate.
[0114] [Polyamide (D)]
[0115] ・D-1: Nylon 6 (manufactured by Ube Industries, Ltd.).
[0116] [carboxylic acid]
[0117] ・Lower fatty acids: acetic acid
[0118] ・Higher fatty acids: stearic acid.
[0119] [Phosphoric acid compounds]
[0120] ・Phosphoric acid.
[0121] <Evaluation method 1>
[0122] (1-1) Quantification of metal atoms and phosphorus
[0123] 0.5 g of the resin composition pellets obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-7 were added to a Teflon (registered trademark) pressure-resistant container manufactured by Aquatech, and 5 mL of nitric acid for precision analysis manufactured by Fujifilm and Koho Pure Chemical Industries, Ltd. was added. After standing for 30 minutes, the container was capped with a cover plate (cap lip) with an explosion-proof membrane, and the microwave high-speed decomposition system "Spider-Wave MWS-2" manufactured by Aquatech was used to decompose the pellets at 150 ° C and 10 minutes, followed by 180 ° C and 10 minutes. In the case where the decomposition of the resin composition pellets is insufficient, the treatment conditions are appropriately adjusted. The contents after the decomposition treatment were diluted with 10 mL of ion exchange water, and all the liquid was transferred to a 50 mL volumetric flask, and the volume was constant with ion exchange water to obtain a decomposition solution. The decomposed solution was measured using an ICP emission spectrometer "Optima 4300 DV" manufactured by Parkin Elmer Japan, and the metal atom-equivalent amount of each metal compound and the phosphorus atom-equivalent content of the phosphate compound were quantified.
[0124] (1-2) Quantification of carboxylic acids
[0125] 10 g of the resin composition pellets obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-7 and 50 mL of pure water were put into a 100 mL conical flask with a stopper, a cooling condenser was installed, and the mixture was stirred at 95° C. for 8 hours to obtain an extract. After the obtained extract was cooled to 20° C., it was titrated with a 0.02 mol / L aqueous sodium hydroxide solution using phenolphthalein as an indicator to calculate the acid amount. The value obtained by subtracting the acid amount derived from the quantified phosphoric acid compound from the obtained acid amount was used as the equivalent of the carboxylic acid amount, and the carboxylic acid amount contained in the resin composition was quantified according to the molecular weight of the carboxylic acid used.
[0126] (1-3) Long-term operation evaluation
[0127] The resin composition pellets obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-7 were used to continuously produce a 20 μm single-layer film using a single-screw extruder (Toyo Seiki Co., Ltd., D2020, D (mm) = 20, L / D = 20, compression ratio = 3.5, screw: full spiral). The extrusion conditions are as follows.
[0128] Extrusion temperature: 210℃
[0129] Mould width: 30cm
[0130] Pulling roller temperature: 80℃
[0131] Screw speed: 40rpm
[0132] Pulling roll speed: 3.1 m / min.
[0133] The monolayer film obtained 30 minutes and 8 hours after the start of film formation was sampled into 10 cm × 10 cm samples, and the number of particles that can be visually confirmed (about 50 μm or more) was counted by visual inspection. The increase rate of gel particles was calculated using the following formula and evaluated according to the following criteria. Among the following criteria, A, B, and C are usable levels.
[0134] Increase rate of gel particles = (10 cm obtained 8 hours after the start of film formation) 2 The number of gel particles in the single-layer film) / (the number of 10 cm obtained 30 minutes after the film formation started) 2 The number of gel particles in a single film
[0135] Judgment: Benchmark
[0136] A: The increase rate of gelatinous particles is less than 2
[0137] B: The increase rate of gel particles is 2 or more and less than 4
[0138] C: The increase rate of gel particles is 4 or more and less than 6
[0139] D: The increase rate of gel particles is 6 or more and less than 8
[0140] E: The increase rate of the gel-like particles is 8 or more.
[0141] (1-4) Hue
[0142] Using the resin composition pellets obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-7, a single-layer film with a thickness of 20 μm was prepared as described in the film-making method described in the evaluation method "(1-3) Long-term operability evaluation", and the film was wound on a paper tube with a diameter of 9 cm for 20 m after 1 hour from the start of film-making. The YI value (YI1) of the center of the width direction of the wound roller and the YI value (YI2) at a position 3 cm away from the end of the film were measured using a colorimeter NF-902 (manufactured by Nippon Denshoku Industries) according to the method described in JIS K 7373, and the YI ratio of the center of the film to the end was calculated using the following formula, and the evaluation was performed according to the following criteria. Among the following criteria, A, B, and C are usable levels.
[0143] YI ratio = (YI2-YI1) / YI1
[0144] Judgment: Benchmark
[0145] A: YI ratio is less than 1.0
[0146] B: YI ratio is 1.0 or more and less than 1.5
[0147] C: YI ratio is 1.5 or more and less than 2.0
[0148] D: YI ratio is 2.0 or more and less than 2.5
[0149] E: The YI ratio is 2.5 or more.
[0150] (1-5) Oxygen permeability (OTR)
[0151] Using the resin composition pellets obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-7, a single-layer film having a thickness of 20 μm was prepared in the same manner as the film-forming method described in the above-mentioned evaluation method "(1-3) Evaluation of long-term operability", and the obtained single-layer film was measured using an oxygen permeability measuring device "OX-TRAN 2 / 20" manufactured by MOCON INC. (detection limit: 0.01 cc・20 μm / (m 2 ・day・atm)) at 20°C and 85%RH according to the method described in JIS K 7126 (isobaric method). The oxygen barrier properties are determined according to the following criteria. Among the following criteria, A, B, and C are usable levels.
[0152] Judgment: Benchmark
[0153] A: less than 1.1
[0154] B: 1.1 or more and less than 1.3
[0155] C: 1.3 or more and less than 1.5
[0156] D: 1.5 or above.
[0157] (Unit: cc・20μm / m 2 ・day・atm)
[0158] <Example 1-1>
[0159] A water-containing EVOH pellet having an ethylene unit content of 27 mol% and a saponification degree of 99.9 mol% was placed in an aqueous solution containing acetic acid and a monovalent metal compound (C-1) (sodium acetate), and after being immersed while stirring at 25°C for 6 hours, the pellet was dehydrated, dried at 80°C for 4 hours using a hot air dryer ("DN6101" manufactured by Yamato Scientific Co., Ltd.), and then dried at 120°C for 40 hours to obtain a dry EVOH pellet (water content of 0.25%). It should be noted that the concentrations of acetic acid and the monovalent metal compound (C-1) in the aqueous solution containing acetic acid and the monovalent metal compound (C-1) were appropriately adjusted in the manner described in Table 1 in the resin composition pellets 1-1 obtained in this example.
[0160] For the obtained dry EVOH pellets, 24 ppm of divalent metal hydroxide (B-1) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., magnesium hydroxide) and 1.2 ppm of stearic acid were dry-mixed, and then melt-extruded at a melt temperature of 210°C and an extrusion speed of 20 kg / hr using a twin-screw extruder "TEX30α" (screw diameter of 30 mm) manufactured by Nippon Steel Works, Ltd. The extruded strands were cooled and solidified in a cooling tank, and then cut to obtain resin composition pellets 1-1. It should be noted that a forward kneading disk with L (screw length) / D (screw diameter) = 3 was used. Resin composition pellets 1-1 are a resin composition comprising EVOH (A-1), divalent metal hydroxide (B-1), a monovalent metal compound (C-1), acetic acid and stearic acid, and the EVOH (A-1) is EVOH having an ethylene unit content of 27 mol% and a saponification degree of 99.9 mol%. The obtained resin composition pellets 1-1 had a moisture content of 0.20% and a melt flow rate of 3.9 g / 10 min at 210° C. and a load of 2160 g.
[0161] The obtained resin composition pellet 1-1 was subjected to quantification of metal atoms, quantification of carboxylic acid, long-term running performance evaluation, and measurement of hue and oxygen permeability according to the methods described in the above evaluation methods "(1-1) to (1-5)". It should be noted that the quantitative results of carboxylic acid took into account the value calculated from the amount of carboxylic acid used in the raw materials. The results are shown in Table 1.
[0162] <Examples 1-2 to 1-18, Comparative Examples 1-2 to 1-7>
[0163] As shown in Table 1, except for changing the type and content of the divalent metal hydroxide (B), the content of the monovalent metal compound (C), the content of the carboxylic acid and the content of the phosphoric acid, the same method as in Example 1 was used to prepare the resin composition pellets 1-2 to 1-18 of the example and the resin composition pellets C1-2 to C1-7 of the comparative example, and they were evaluated. Phosphoric acid is contained by mixing phosphoric acid into the solution to be immersed in the aqueous EVOH pellets. The evaluation results are shown in Table 1. It should be noted that the color of Example 1-18 containing phosphoric acid is particularly excellent compared with Example 1-8 not containing phosphoric acid.
[0164] <Comparative Example 1-1>
[0165] A water-containing EVOH pellet having an ethylene unit content of 27 mol% and a saponification degree of 99.9 mol% was placed in an aqueous solution containing acetic acid and a monovalent metal salt (C-1), and after immersion while stirring at 25°C for 6 hours, the pellet was dehydrated, dried at 80°C for 4 hours using a hot air dryer ("DN6101" manufactured by Yamato Scientific Co., Ltd.), and then dried at 120°C for 40 hours to obtain a dry EVOH pellet (water content of 0.25%). It should be noted that the concentrations of acetic acid and the monovalent metal salt (C-1) in the aqueous solution containing acetic acid and the monovalent metal salt (C-1) were appropriately adjusted in the manner described in Table 1 in the resin composition pellets C1-1 obtained in this comparative example.
[0166] For the obtained dry EVOH pellets, after dry-mixing stearic acid 1.2ppm, a twin-screw extruder "TEX30α" (screw diameter 30mm) manufactured by Nippon Steel Works, Ltd. was used to melt extrude at a melting temperature of 210°C and an extrusion speed of 20kg / hr. In addition, a substance obtained by making a metal compound (B'-9) into an aqueous solution was added to the twin-screw extruder using a liquid adding pump in such a way that the metal concentration of the resin composition pellets C1-1 becomes the concentration recorded in Table 1, and the extruded strands were cooled and solidified in a cooling tank, and then cut to obtain resin composition pellets C1-1. It should be noted that a forward kneading disk having a screw structure of L (screw length) / D (screw diameter) = 3 was used on the downstream side of the aforementioned liquid adding pump. The resin composition pellet C1-1 is a resin composition comprising EVOH (A-1), a divalent metal compound (B'-9), a monovalent metal compound (C-1), acetic acid and stearic acid, wherein the EVOH (A-1) is EVOH having an ethylene unit content of 27 mol% and a saponification degree of 99.9 mol%. The obtained resin composition pellet C1-1 has a moisture content of 0.20% and a melt flow rate of 3.9 g / 10 min at 210°C and a load of 2160 g. The obtained resin composition pellet C1-1 was evaluated using the same method as in Example 1. The results are shown in Table 1.
[0167] <Evaluation method 2>
[0168] (2-1) Long-term operability evaluation
[0169] The resin composition pellets obtained in Examples 2-1 to 2-21 and Comparative Examples 2-1 to 2-6 were used to continuously produce a 20 μm single-layer film using a single-screw extruder (Toyo Seiki Co., Ltd., D2020, D (mm) = 20, L / D = 20, compression ratio = 3.5, screw: full spiral). The extrusion conditions are as follows.
[0170] Extrusion temperature: 230℃
[0171] Mould width: 30cm
[0172] Pulling roller temperature: 80℃
[0173] Screw speed: 40rpm
[0174] Pulling roll speed: 3.1 m / min.
[0175] The monolayer film obtained 30 minutes and 4 hours after the start of film formation was sampled into 10 cm × 10 cm samples, and the number of particles that can be visually confirmed (about 50 μm or more) was counted by visual inspection. The increase rate of particles was calculated using the following formula and evaluated according to the following criteria. Among the following criteria, A, B, and C are usable levels.
[0176] Particle increase rate = (10 cm obtained 4 hours after the start of film formation) 2 The number of particles in the single-layer film) / (the number of particles in the 10 cm2 film obtained 30 minutes after the film formation started) 2 Number of particles in a single film)
[0177] Judgment: Benchmark
[0178] A: The increase rate of particulate matter is less than 2
[0179] B: The increase rate of particulate matter is greater than 2 and less than 4
[0180] C: The increase rate of particulate matter is 4 or more and less than 6
[0181] D: The increase rate of particulate matter is greater than 6 and less than 8
[0182] E: The increase rate of particulate matter is 8 or more.
[0183] (2-2) Hue
[0184] Using the resin composition pellets obtained in Examples 2-1 to 2-21 and Comparative Examples 2-1 to 2-6, a single-layer film with a thickness of 20 μm was prepared as described in the film-making method described in the evaluation method "(2-1) Long-term runnability evaluation", and the film was wound on a paper tube with a diameter of 9 cm for 20 m after 1 hour from the start of film-making. The YI value (YI1) of the center of the width direction of the wound roller and the YI value (YI2) at a position 3 cm away from the end of the film were measured using a colorimeter NF-902 (manufactured by Nippon Denshoku Industries) according to the method described in JIS K 7373, and the YI ratio of the center of the film to the end was calculated using the following formula, and the evaluation was performed according to the following criteria. Among the following criteria, A, B, and C are usable levels.
[0185] YI ratio = (YI2-YI1) / YI1
[0186] Judgment: Benchmark
[0187] A: YI ratio is less than 1.0
[0188] B: YI ratio is 1.0 or more and less than 1.5
[0189] C: YI ratio is 1.5 or more and less than 2.0
[0190] D: YI ratio is 2.0 or more and less than 2.5
[0191] E: The YI ratio is 2.5 or more.
[0192] (2-3) Retort resistance
[0193] Using the resin composition pellets obtained in Examples 2-1 to 2-21 and Comparative Examples 2-1 to 2-6, a single-layer film with a thickness of 20 μm was prepared in the same manner as the film-forming method described in the above-mentioned evaluation method "(2-1) Evaluation of long-term operability", and the obtained single-layer film, a biaxially stretched nylon 6 film ("Enblem ONBC" manufactured by Unichika Co., Ltd., with a thickness of 15 μm) and an unstretched polypropylene film ("RXC-22" manufactured by Mitsui Chemicals Toselo Co., Ltd., with a thickness of 50 μm) were cut into A4 size, respectively, and an adhesive for dry lamination was applied to both surfaces of the single-layer film, and dry lamination was carried out in such a manner that the outer layer became a nylon 6 film and the inner layer became an unstretched polypropylene film, and the film was dried at 80° C. for 3 minutes to obtain a transparent laminated film comprising three layers. As the dry lamination adhesive, an adhesive having "Takelac A-520" from Mitsui Chemicals as a base agent, "Takenet A-50" from Mitsui Chemicals as a curing agent, and ethyl acetate as a diluent was used. The coating amount of the adhesive was set to 4.0 g / m 2 After lamination, the laminate was cured at 40°C for 3 days.
[0194] Two sheets of the laminated film obtained above were used to make a four-side sealed soft bag with an external size of 12 cm × 12 cm. The content was set to water. A cooking device (high temperature and high pressure cooking sterilization tester "RCS-40RTGN" of Nisaka Manufacturing Co., Ltd.) was used to perform a cooking treatment at 120°C for 120 minutes. After the cooking treatment, the surface water was wiped off, and after being placed in a constant temperature and humidity room at 20°C and 65% RH for 1 day, the appearance characteristics were judged according to the following criteria as an evaluation of the cooking resistance. Among the following judgment criteria, A is a level that can be used.
[0195] Judgment: Benchmark
[0196] A: No whitening
[0197] B: Striped whitening
[0198] C: About 25% of the soft bag surface is whitened
[0199] D: Half of the soft bag surface is whitened
[0200] E: Almost the entire surface of the soft bag is whitened.
[0201] (2-4) Oxygen Permeability (OTR)
[0202] The resin composition pellets obtained in Examples 2-1 to 2-21 and Comparative Examples 2-1 to 2-6 were used to prepare a single-layer film having a thickness of 20 μm in the same manner as the film-forming method described in the above-mentioned evaluation method "(2-1) Evaluation of long-term operability". The obtained single-layer film was measured using an oxygen permeability measuring device "OX-TRAN 2 / 20" manufactured by MOCON INC. (detection limit: 0.01 cc・20 μm / (m 2 ・day・atm)) at 20°C and 85%RH according to the method described in JIS K 7126 (isobaric method). The oxygen barrier properties are determined according to the following criteria. Among the following criteria, A, B, and C are usable levels.
[0203] Judgment: Benchmark
[0204] A: less than 2.1
[0205] B: 2.1 or more and less than 2.3
[0206] C: 2.3 or more and less than 2.5
[0207] D: 2.5 or above.
[0208] (Unit: cc・20μm / m 2 ・day・atm)
[0209] (2-5) Average dispersed particle size
[0210] The resin composition pellets of each embodiment or comparative example were embedded with epoxy resin, and transverse slices were made using a microtome. The obtained transverse slices were electron stained in a 5% phosphotungstic acid aqueous solution for 3 minutes, and the sample thus obtained was dried and observed using a transmission electron microscope (TEM) "JEM2100F" manufactured by JEOL Ltd. at an observation magnification of 20,000 times. During the observation, the dispersed particle size was measured for 100 PA particles, and the average value was calculated as the average dispersed particle size. It should be noted that when observing using TEM, EVOH was observed as the bright contrast portion of the photograph, and PA was observed as the dark contrast portion.
[0211] (Example 2-1)
[0212] The hydrous EVOH pellets having an ethylene unit content of 27 mol% and a saponification degree of 99.9 mol% were put into an aqueous solution containing acetic acid and a monovalent metal compound (C-1) (sodium acetate), and after being immersed while stirring at 25°C for 6 hours, the pellets were dehydrated, dried at 80°C for 4 hours using a hot air dryer (DN6101 manufactured by Yamato Scientific Co., Ltd.), and then dried at 120°C for 40 hours to obtain dry EVOH pellets (water content of 0.25%). It should be noted that the concentrations of acetic acid and the monovalent metal compound (C-1) in the aqueous solution containing acetic acid and the monovalent metal compound (C-1) were appropriately adjusted in the manner described in Table 2 as the contents in the resin composition pellets 2-1 obtained in this example.
[0213] 108 ppm of divalent metal hydroxide (B-1) (magnesium hydroxide, aspect ratio of 10) and 5.5 ppm of stearic acid were added to 100 parts by mass of the obtained dried EVOH pellets 90 parts by mass and PA (D-1) (UBE NYLON SF1018A), and dry-mixed. Then, melt extrusion was performed at a melt temperature of 230°C and an extrusion rate of 20 kg / hr using a twin-screw extruder "TEX30α" (screw diameter of 30 mm) manufactured by Nippon Steel Works, Ltd. The extruded strands were cooled and solidified in a cooling layer, and then cut to obtain resin composition pellets 2-1. It should be noted that as the screw of the extruder, a forward kneading disk having L (screw length) / D (screw diameter) = 3 was used. The resin composition pellet 2-1 is a resin composition comprising EVOH (A-1), PA (D-1), a divalent metal hydroxide (B-1), a monovalent metal compound (C-1), acetic acid and stearic acid, wherein the EVOH (A-1) is EVOH having an ethylene unit content of 27 mol% and a saponification degree of 99.9 mol%. The moisture content of the resin composition pellet 2-1 is 0.20%, and the melt flow rate at 230°C and a load of 2160 g is 6.0 g / 10 minutes.
[0214] The obtained resin composition pellets 2-1 were subjected to quantification of metal atoms, quantification of carboxylic acids, long-term running performance evaluation, and hue, retort resistance, and oxygen permeability evaluation according to the methods described in the above evaluation methods "(1-1), (1-2), (2-1) to (2-4)". It should be noted that the quantification results of carboxylic acids took into account the values calculated from the amount of carboxylic acids used in the raw materials. The results are shown in Table 2.
[0215] <Examples 2-2 to 2-21, Comparative Examples 2-1 to 2-6>
[0216] As shown in Table 2, except for changing the content of PA (D), the type and content of the divalent metal hydroxide (B), the type and content of the monovalent metal compound (C), the content of the carboxylic acid and the content of the phosphoric acid, the resin composition pellets 2-2 to 2-21 of the embodiment and the resin composition pellets C2-1 to C2-6 of the comparative example were prepared by the same method as in Example 2-1 and evaluated. Phosphoric acid is contained by mixing phosphoric acid into the solution to be immersed in the aqueous EVOH pellets. The evaluation results are shown in Table 2. It should be noted that Example 2-20 containing phosphoric acid has a particularly excellent hue compared to Example 2-8 not containing phosphoric acid. The following evaluations were performed for Example 2-21 and Example 2-10.
[0217] (Evaluation) The soft bag subjected to retort treatment according to the above evaluation method "(2-3) Retort resistance evaluation" was opened and cut into a size of 5 cm × 7 cm. The haze of the cut sample was measured according to JIS K 7105 using a reflectance / transmittance meter ("HR-100" manufactured by Murakami Color Laboratory Co., Ltd.).
[0218] The evaluation results confirmed that the haze value of Example 2-21 having a high polyamide content was 21.5, and the haze value of Example 2-10 was 23.6, and that Example 2-21 having a high polyamide content was excellent in transparency.
[0219]
[0220]
Claims
1. A resin composition comprising an ethylene-vinyl alcohol copolymer (A) having an ethylene unit content of 20 mol% or more and 60 mol% or less, a divalent metal hydroxide (B), a monovalent metal compound (C) and a polyamide resin (D), wherein the content of the divalent metal hydroxide (B) is 5 ppm or more and 5000 ppm or less, and a mass ratio C / B of the monovalent metal atom equivalent amount of the monovalent metal compound (C) to the divalent metal atom equivalent amount of the divalent metal hydroxide (B) is 0.025 to 100, The divalent metal atom constituting the divalent metal hydroxide (B) includes at least one selected from the group consisting of magnesium, calcium, iron and zinc, The monovalent metal atom constituting the monovalent metal compound (C) includes at least one selected from the group consisting of sodium, potassium, lithium, rubidium and cesium, The monovalent metal compound (C) is at least one selected from the group consisting of salts of organic acids, salts of inorganic acids, and metal complexes.
2. The resin composition according to claim 1, wherein The mass ratio A / D of the ethylene-vinyl alcohol copolymer (A) to the polyamide resin (D) is 55 / 45 to 99 / 1.
3. The resin composition according to claim 1 or 2, comprising a matrix phase comprising an ethylene-vinyl alcohol copolymer (A) and a dispersed phase comprising a polyamide resin (D), wherein the dispersed phase comprising the polyamide resin (D) has an average dispersed particle size of 2 μm or less.
4. The resin composition according to claim 1 or 2, wherein 95% by mass or more of the thermoplastic resin constituting the resin composition is the ethylene-vinyl alcohol copolymer (A).
5. The resin composition according to claim 1 or 2, wherein 95% by mass or more of the thermoplastic resin constituting the resin composition is the ethylene-vinyl alcohol copolymer (A) and the polyamide resin (D).
6. The resin composition according to claim 1 or 2, wherein The content of the monovalent metal compound (C) in terms of monovalent metal atoms is 5 ppm or more and 1000 ppm or less.
7. The resin composition according to claim 1 or 2, wherein The ratio of magnesium atoms in all metal atoms constituting the divalent metal hydroxide (B) is 80 mol% or more. The resin composition according to claim 1 or 2, comprising a carboxylic acid.
9. The resin composition according to claim 8, wherein A higher fatty acid is contained as the carboxylic acid, and the content of the higher fatty acid is 0.1 ppm or more and 250 ppm or less. 10 . The resin composition according to claim 1 , comprising a phosphoric acid compound.
11. The resin composition according to claim 1 or 2, wherein The aspect ratio of the divalent metal hydroxide (B) is 3 or more and 500 or less. 12 . A molded article comprising the resin composition according to claim 1 . 13 . A multilayer structure comprising a layer made of the resin composition according to claim 1 .
Citation Information
Patent Citations
Resin composition and molded article
WO2017110568A1
Saponified ethylene-vinyl ester copolymer resin composition and multilayer structure using the composition
US20130065001A1